New Quaternary Compounds R3Ni0.5SiS7 (R – Y, Sm, La) with the La3Mn0.5SiS7 Structure - Smitiukh, Oleksandr; Marchuk, Oleg (Physics and Chemistry of Solid State, 2022)
The new sulfides Y3Ni0.5SiS7, Sm3Ni0.5SiS7, and La3Ni0.5SiS7 exist in the quasi-ternary systems Y2S3 – NiS – SiS2, Sm2S3 – NiS – SiS2, and La2S3 – NiS – SiS2, respectively, for which the isothermal sections at 770 K were investigated. The crystal structure of the sulfides was determined by the X-ray powder method. It belongs to the La3Mn0.5SiS7 structure type (S.G. Р63; Pearson symbol hP23), with the lattice parameters а = 0.97643(4) nm; с = 0.56377(4) nm (Y3Ni0.5SiS7), а = 0.99599(8) nm; с = 0.56583(5) nm (Sm3Ni0.5SiS7), and а = 1.02830(6) nm; с = 0.57412(4) nm (La3Ni0.5SiS7). The structure of obtained sulfides is as follows: Y, Sm, and La atoms are located in the 6с site and center trigonal prisms with two additional S atoms. Ni atoms occupy the 2а site (0.5 occupancy) and have octahedral surrounding of S atoms. The coordination number of Si atoms (the 2b site) is 4. The Ni-centered octahedra form infinite chains [Ni 6S]n.